PENGGUNAAN MEDIA LAGU ANAK-ANAK DALAM MENGEMBANGKAN KEMAMPUAN KOSAKATA BAHASA INGGRIS SISWA DI PAUD - Ira, Engliana2 Fitri Senny Hapsari3 Miranti (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2015)
Abstract: The purpose of the public service activity was to improve the young children ability in English Vocabulary. The media used in this acitivity is children English songs for teaching vocabulary. The participants of this activity were 2 teachers and 20 children who live at Cibeurem Cisarua Bogor. The result of this activity was an improved teaching ability of the teachers and the good ability of young learners in catching the learning material. Keywords : Media songs Children , Vocabulary , ECD